2007
DOI: 10.1289/ehp.9488
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Study of Urinary Biomarkers of Phytoestrogens, Phthalates, and Phenols in Girls

Abstract: BackgroundHormonally active environmental agents have been measured among U.S. children using exposure biomarkers in urine. However, little is known about their variation by race, age, sex, and geography, and no data exist for newly developed biomarkers.ObjectiveOur goal was to characterize relevant, prevalent exposures for a study of female pubertal development.MethodsIn a pilot study among 90 girls from New York City, New York, Cincinnati, Ohio, and northern California, we measured 25 urinary analytes repres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
144
5
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 225 publications
(167 citation statements)
references
References 20 publications
17
144
5
1
Order By: Relevance
“…A few recent epidemiologic studies have suggested that prenatal and childhood exposure to some of these phenols (or their precursors) may be associated with altered neurodevelopment, obesity, and precocious puberty (11,26,(61)(62)(63)(64). Therefore, our findings confirming that these chemicals not only are present in U.S. children's urine (6)(7)(8)(9)(10)(11)(12)(13)(14), but also could circulate in blood warrant additional research to further evaluate the potential effects on human health upon exposure to these compounds (or their precursors).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…A few recent epidemiologic studies have suggested that prenatal and childhood exposure to some of these phenols (or their precursors) may be associated with altered neurodevelopment, obesity, and precocious puberty (11,26,(61)(62)(63)(64). Therefore, our findings confirming that these chemicals not only are present in U.S. children's urine (6)(7)(8)(9)(10)(11)(12)(13)(14), but also could circulate in blood warrant additional research to further evaluate the potential effects on human health upon exposure to these compounds (or their precursors).…”
Section: Discussionsupporting
confidence: 78%
“…Of interest, NHANES urinary data for triclosan, methyl paraben, propyl paraben and the two dichlorophenols also suggest widespread exposure to these compounds or their precursors in the U.S. general population at least since 2003 (10). Together these findings suggest that, despite the non-persistent physicochemical characteristics (e.g., rapid metabolism in humans) and the likely episodic nature of the exposures to triclosan, methyl paraben, and propyl paraben or to the precursors of 2,4-dichlorophenol and 2,5-dichlorophenol, trace concentrations of these chemicals are not only detectable in urine of young children (6)(7)(8)(9)(10)(11)(12)(13)(14), but can also be detected in blood.…”
Section: Discussionmentioning
confidence: 91%
“…However, specific data on socioeconomic indicators and covariates prior to the participants' study entry at age 9 or 10 were not available and, therefore, were not evaluated in our analysis. While we were able to adjust for a number of potential explanatory variables linking SES and menarche, including anthropometric factors, we were unable to probe exposure to hormonally active environmental agents [36] as potential mediators of the association between SES and age at menarche.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the only published study that completely failed to detect or measure any form of BPA in urine samples from environmentally exposed individuals. Volkel et al (2005) used HPLC-MS/MS; this is the same technique that was used in several other studies in which unconjugated and conjugated BPA were detected in urine Hong et al 2009;Mahalingaiah et al 2008;Nepomnaschy et al 2009;Teitelbaum et al 2008;Wolff et al 2007;Yang YJ et al 2009;Ye et al 2009a). Why did Volkel et al (2005) not detect any form of BPA?…”
Section: Exposure Assessment From Urinary Measures Of Bpamentioning
confidence: 99%